Temporal dynamics of Ganoderma basal stem rot (BSR) disease progress in oil palm: Effects of planting generation, topography, and previous crop - Nur Aliyah Jazuli; Assis Kamu (RSIS International, 2025)
Ganoderma basal stem rot (BSR) disease poses a major threat to oil palm plantations in Southeast Asia. This study examined how BSR disease progress, quantified using the area under the disease progress (AUDPC), varies with planting generation, topography, and previous crop. Data from 1,184 palms in Sabah, Malaysia were analyzed using non-parametric statistical tests due to non-normal distribution. Results showed significantly higher AUDPC in second-generation palms, replanting's after oil palm, and flat to undulating terrain. These findings highlight the importance of considering replanting history and site conditions when managing BSR in oil palm plantations.